The Status of Foreign Labor Migration of Bardiya District in Nepal - Neupane, Bed Prasad (Journal of Population and Development, 2020)
This research paper attempts to describe the overseas migration of Bardiya District in Nepal. The main objective of this study is to examine the foreign labor migration from Nepal to Gulf countries including Malaysia. Among many other castes/ethnicities in Nepal, Tharu caste occupies the high percentage. The population of Tharu caste is 56,062 in the study area. Majority of the Tharu people are involved in agriculture sector as it is the traditional occupation. Moreover, this community holds less percentage of agriculture land in the study area. They are still farming the land with conservative and traditional methods and they are far from the modern technology of agriculture. Due to unemployment and insufficient agricultural land, most of the Tharu people migrate to Gulf countries. Selection for Gulf countries as destination by Tharu people in the study area is due to the low privilege households and lack of skill in this manpower. The Government of Nepal should guarantee/manage safer and better foreign labor migration especially in such type of caste/ethnicity.